PATHOLOGY OF ENDOCRINE SYSTEM: ETIOLOGY AND PATHOGENESIS OF ENDOCRINOPATHIES. DISORDERS OF HYPOTHALAMOHYPOPHYSIAL SYSTEM - P.F. Litvitskiy ("Paediatrician" Publishers LLC, 2011)
The first lection in the course «Endocrinopathies» discusses main rules of endocrinology, main causes and key stages of endocrine pathology development, etiology and pathogenesis of the most frequent hypophysial disorders with their symptoms and mechanisms, and several types of adenohypophysial pathology. Author gives some tests and situational tasks for the evaluation of the level of knowledge, and the answers to the tests.Key words: endocrinopathy, hypopituitarism, hyperpituitarism, acromegalia, diabetes insipidus, syndrome of inadequate secretion of ADH.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2011; 10 (4): 47-60)